2009
DOI: 10.1021/ma901210u
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Mechanistic Aspects of Ethylene and Acrylates Catalytic Copolymerization in Solution and in Emulsion

Abstract: Ethylene was copolymerized with acrylates in solution and in emulsion using sulfonated arylphosphine Pd-based catalysts. The copolymerization of C 2 H 4 and methyl acrylate in toluene was slowed by the σ-coordination of the acrylate on Pd. The substitution of pyridine by itself was shown to proceed via an associative mechanism with activation parameters ΔH ‡ =16.8 kJ/mol and ΔS ‡ =-98 J mol -1 K -1 whereas the activation parameters for the substitution of pyridine by methyl acrylate were found to be ΔH ‡ =18.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…3 10 À2 mol L À1 in CDCl 3 ) is contacted with pyridine (0.45 equiv), lutidine is displaced quantitatively by pyridine, as expected for steric reasons (shorter Pd À N bonds for related pyridine complexes (except for complex 2 f-pyr; see Table 1). This ligand substi- , see the Supporting Information) as we [9] and Conley et al [16] have shown that ligand exchange occurs through an associative bimolecular pathway for palladium phosphanesulfonates. This relatively low value of k contrasts with the value of 2.3 10 5 L mol À1 s reported by us for pyridine exchange at 4 8C for catalyst 2 a-pyr.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…3 10 À2 mol L À1 in CDCl 3 ) is contacted with pyridine (0.45 equiv), lutidine is displaced quantitatively by pyridine, as expected for steric reasons (shorter Pd À N bonds for related pyridine complexes (except for complex 2 f-pyr; see Table 1). This ligand substi- , see the Supporting Information) as we [9] and Conley et al [16] have shown that ligand exchange occurs through an associative bimolecular pathway for palladium phosphanesulfonates. This relatively low value of k contrasts with the value of 2.3 10 5 L mol À1 s reported by us for pyridine exchange at 4 8C for catalyst 2 a-pyr.…”
Section: Resultsmentioning
confidence: 63%
“…This relatively low value of k contrasts with the value of 2.3 10 5 L mol À1 s reported by us for pyridine exchange at 4 8C for catalyst 2 a-pyr. [9] For 2 a-pyr, free pyridine is in rapid exchange with bound pyridine at room temperature (coalescence at À50 8C), as observed by 1 H NMR spectroscopy, whereas for catalyst 2 h-pyr, free pyridine and bound pyridine are in the slow exchange regime at 50 8C. For catalyst 2 f-pyr, coalescence is not yet reached at room temperature in CDCl 3 , and coalescence between free and bound pyridine occurs at 60 8C in C 2 D 2 Cl 4 (the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[15] These studies employ the catalyst [(oAr 2 PC 6 H 4 SO 3 )PdMe(L)] with Ar = o-OMePh, which corresponds to the ligand originally presented by Drent. [5] The role of the ancillary ligand L (L = pyridine, [12,16] lutidine, [17] DMSO, [15] or allyl group [11] ) on the catalytic activity has been studied in detail. However, at this time, little is known on the influence of the arylphosphane sulfonate structure.…”
Section: Introductionmentioning
confidence: 99%